MicroRNA-204-3p modulates epithelial-mesenchymal transition by targeting paired box gene 2 in human melanoma A-375 cells - Song, Jun; Chen, Xinyan; Zhang, Liping; Song, Dandan; Xiong, Huizi (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Background: Paired box 2 gene promoted the progression of subsequent epithelial-mesenchymal transition (EMT) in malignant melanoma, which is the most dangerous type of skin cancer. We aimed to investigate the functional role of miR-204-3p in metastatic melanoma. Methods: To study the effects of overexpressed miR-204-3p on the melanoma cells, miR-204-3p mimic vector were transfected into A-375 cells for detecting the cell viability using CCK-8 kit. Wound healing and Transwell assays were performed to assess the migration and invasion capacities of melanoma cells. TargetScan and miRTarBase were used to predict the potential target of miR-204-3p, which was subsequently verified by dual-luciferase assay. The expressions of several EMT-associated genes were determined by quantitative real-time polymerase chain (qRT-PCR) and Western blot. Results: The expression of miR-204-3p in several melanoma cell lines was lower than that in HaCaT cells. After transfecting with the miR-204-3p mimic vector, the cell viability of A-375 cells decreased over time and significantly reduced at 48 h (P